1998
DOI: 10.1002/(sici)1520-636x(1998)10:7<578::aid-chir5>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Chirality and insect pheromones

Abstract: Enantioselective synthesis is a central component of research on the effect of chirality on the relationships between pheromone structure and pheromone bioactivity. The syntheses of stegobinone, the drugstore beetle pheromone, and frontalin, a bark beetle pheromone, are reported as examples of stereocontrolled synthesis. Chirality governs the biodiversity of pheromone perception, as illustrated by the discussion on the relationships between absolute configuration and pheromone activity. Chirality 10: 578-586, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Although chiral alcohols 1 and 2 seem to play a minor role compared with the major component (i.e., compounds 1 and 2 are less abundant in the extracts and less attractive than compound 4), the absolute configuration of naturally occurring chiral pheromones is essential to have a complete understanding of the relationship between structure and behavioural effects (Mori, 1998). Our preliminary data showed that S .…”
Section: Discussionmentioning
confidence: 99%
“…Although chiral alcohols 1 and 2 seem to play a minor role compared with the major component (i.e., compounds 1 and 2 are less abundant in the extracts and less attractive than compound 4), the absolute configuration of naturally occurring chiral pheromones is essential to have a complete understanding of the relationship between structure and behavioural effects (Mori, 1998). Our preliminary data showed that S .…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1970s, enantioselectivity of insect [3] olfactory systems has been well documented. Evidence ranges from enantiomer driven behaviors [4], [5], [6], [7], [8] and glomerular activation patterns [9] to highly specific olfactory receptor cells for pheromones and plant odorants [10], [11]. In fact, behavioral studies carried out in humans [2], honeybees [12] and mice [13] have clearly demonstrated the ability of these organisms to distinguish between chiral odorants, prompting several authors to postulate the existence of enantioselective ORs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the male pine engraver beetle ( Ips pini ) use one enantiomer (−)‐ipsdienol, the naturally occurring enantiomer, to attract conspecific females . This beetle is a parasitic species managed partially using pheromones, which must be applied at the correct ratio of enantiomers . The process of identifying pheromones has been accelerated in recent years due to advances in modern spectroscopic and stereoselective synthesis methods .…”
Section: Introductionmentioning
confidence: 99%